Graphene: A new technology for agriculture - May, André (2021)
This article presents a review on the use of graphene in various segments, elucidating that this product can be used in various industrial sectors. These include mainly agriculture (as in large crops of high relevance, such as coffee), the food industry and the environment, as a plant growth stimulator and in fertilizers, nanoencapsulation and smart-release systems, antifungal and antibacterial agents, smart packaging, water treatment and ultrafiltration, contaminant removal, pesticide and insecticide quantitation, detection systems and precision agriculture. However, some challenges can be overcome before the graphene-based nanoparticle is used on a large scale. In this way, before using the product in the environment, it is necessary to determine whether the technology is safe for the soil-plant system and consumers. Furthermore, the cost of its use can also be a limiting factor depending on the level applied. Therefore, this review proposes to examine the diverse literature to explain the effects of the use of graphene in agriculture, plants and soil microorganisms. Accordingly, this article discusses and presents the possibilities of application of graphene in agriculture, plants and soil microorganisms.